"The glue that makes the glitter stick": Preliminary outcomes associated with a trauma-informed, resiliency-based, interprofessional graduate course for child welfare, mental health, and education. Issue 3 (27th May 2019) - Woodside-Jiron, Haley; Jorgenson, Simon; Strolin-Goltzman, Jessica; Jorgenson, Jennifer
ABSTRACT: Among school-age children, there is a high prevalence of trauma-related mental health needs across child welfare, mental health, and education settings. The purpose of this manuscript is to describe an interprofessional graduate course which aims to build capacity among community providers to improve well-being for children and families. Specifically, it is the goal of this Academy to increase the number of professionals across professions who enter the field equipped to effectively support the strengths and complex needs of children, youth, and families who have been adversely impacted by trauma. Specifically, this paper will share findings from a pre-experimental study of the "Academy" measuring pre-post change on: (a) trauma knowledge, (b) trauma skills application, (c) job-related self-efficacy, (d) job outcome expectations, and (e) interdisciplinary collaboration and interprofessional practice. Implications for workforce development and system initiatives are discussed. With replication and more rigorous study, the trauma-informed, interprofessional curriculum holds promise.